(untitled) (KONFERENSIYA, 2025)
This article explores the challenges faced by Uzbek-Russian bilinguals in learning English, focusing on linguistic interference, grammar complexities, and pronunciation difficulties. It discusses the impact of their dual-language background on English acquisition and offers real-life examples from Uzbek classrooms. The study highlights practical teaching strategies to overcome these barriers